The Influence of Authoritarian Leadership Style on Employee Performance CV. Globalindo Jaya Palembang - Fanny Andre Dwi Taqwa; Muhammad Wadud; Susi Handayani (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to examine the effect of authoritarian leadership style on employee performance at CV Globalindo Jaya Palembang. The data in this study was obtained through observation, document study, interviews and distributing questionnaires to all members of 32 respondents. The results of the study partially show that the authoritarian leadership style has no significant positive effect on employee performance at CV Globalindo Jaya Palembang. This research is expected to provide benefits to the company in terms of improving employee performance.